Gas production analysis for the buffer layer of high‐voltage cross‐linked polyethylene cables - Wenqing Zhou; Licheng Li; Hao Cheng; Xun Wu; Gang Liu (High Voltage, 2024)
Abstract The cross‐linked polyethylene insulated cables with corrugated aluminium‐sheathed are widely used in urban power systems. Recently, a new type of power cable fault has emerged, primarily due to defects in the buffer layer. However, there is a notable lack of effective evaluation methods for these defects in high‐voltage (HV) cables. Initially, a theoretical analysis of the gas generation mechanism in the cable buffer layer was conducted, identifying distinct gas products at different stages. Subsequently, the diffusion kinetics of gas within the cable was studied, highlighting the importance of gas in determining the state of the buffer layer. The authors then collected and analysed 60 sets of buffer layer gases from two operational 110 kV HV cables using gas chromatography technology. Combining these results with the findings from on‐site inspections, the characteristic gas components and concentration distribution under various defect conditions were summarised. The results found higher concentrations of CH4 in normal cables and defective cables, while there are higher concentrations of H2, CO and CO2 in defective cables, and the oxygen content decreases. The discoveries made in this research may offer a new approach for assessing the state of the cable buffer layer.